Heparin-Induced Osteoporosis in Rats - Matzsch, Thomas; Bergqvist, David; Hedner, Ulla; Nilsson, Bo; Østergaard, Per (Thrombosis and Haemostasis, 1986)
In order to study the effect of heparin in inducing osteoporosis, 30 female rats were divided in two groups and treated with daily injections of 2 IU heparin/g body weight for 33 and 65 days and compared with the same number of rats acting as controls. The mineral bone mass in the femora of the animals was measured quantitatively. A significant (p <0.001) reduction in bone mineral mass was found in the heparin-treated animals. This effect was present to the same degree after 33 days as after 65 days of treatment. It is concluded that heparin in this dose causes osteoporosis in rats after 33 days and that the described method can be used as an experimental model for further studies on this topic.
Keywords: Heparin; Osteoporosis